Qualifications and Concepts an Agricultural Editor Should Bring to the Job - Everett Metcalf (Journal of Applied Communications, 1981)
Several years ago the agricultural information staff at Washington State University listed the qualifications and concepts they felt an agricultural editor should have. Using those two lists as bases, 26 land-grant university agricultural editors - current, retired , and some who moved to other jobs - provided suggestions to make the lists more universally useful. Two deans of agriculture also sent suggestions.